Colloid chemical properties of binary sols as precursors for YAG optical ceramics. Issue 15 (15th November 2016) - Balabanov, Stanislav S.; Gavrishchuk, Evgeny M.; Rostokina, Elena Ye.; Plekhovich, Alexander D.; Kuryakov, Vladimir N.; Amarantov, Sergey V.; Khamaletdinova, Nadiya M.; Yavetskiy, Roman P.
Abstract: The basic colloid chemical characteristics of binary sols as precursors for obtaining of Y3 Al5 O12 (YAG) transparent ceramics have been studied. The effect of the particle size, particle size distribution of sols, electrophoretic mobility of particles, aggregative stability of sols, as well as the calcination temperature on the properties of resulting YAG powders has been determined. The binary sols have been investigated by turbidimetry, electrophoretic light scattering (ELS), dynamic light scattering (DLS) and small-angle X-ray scattering (SAXS) methods. It has been shown that the aggregative stability of binary sols strongly depends on the nature of the precursor. The studied sols of different composition exhibit relatively high stability over time and under action of different physical and chemical factors. The thermal decomposition of YAG xerogels obtained by drying of the binary sols has been studied by thermogravimetry (TG) and differential scanning calorimetry (DSC), X-ray diffraction (XRD) and FTIR spectroscopy methods. The obtained xerogels have been used to produce YAG optical ceramics by the vacuum sintering. It has been shown that only 5AlO(OH)(NO3 )0.07 ·3Y(OH)2 (OOCCH3 ) xerogel ensures fabrication of YAG transparent ceramics with good optical quality.